Gut microbiota supports male reproduction via nutrition, immunity, and signaling - Cai, Hui; Cao, Xuanhong; Qin, Dezhe; Liu, Yundie; Liu, Yang; Hua, Jinlian; Peng, Sha (Frontiers in Microbiology, 2022)
Gut microbiota (GM) is a major component of the gastrointestinal tract. Growing evidence suggests that it has various effects on many distal organs including the male reproductive system in mammals. GM and testis form the gut-testis axis involving the production of key molecules through microbial metabolism or de novo synthesis. These molecules have nutrition, immunity, and hormone-related functions and promote the male reproductive system via the circulatory system. GM helps maintain the integral structure of testes and regulates testicular immunity to protect the spermatogenic environment. Factors damaging GM negatively impact male reproductive function, however, the related mechanism is unknown. Also, the correlation between GM and testis remains to be yet investigated. This review discusses the complex influence of GM on the male reproductive system highlighting the impact on male fertility.